PENETAPAN TARGET PAJAK DAN RETRIBUSI DAERAH - ', Syafrul; Farida, Lena (Jurnal Kebijakan Publik, 2013)
The purpose of this study was to analyzethe targeting of taxes and levies in the field of revenue Revenue Service, Finance and AssetManagement area Siak. This research is a case study using a descriptive analysis comparingtheory with practice. In accordance with the facts on the ground are obtained from target-settingprocess reribusi local taxes and services in the field of revenue income, management, finance andasset Siak area, apparently targeting because: 1) the lack of data, lack of data was the factor thatled to the decision taken in the determination taxes and levies targets seem less rational, since thedetermination based on the realization last year and projected using an average of the targets setin the years to come, 2) lack of human resources, lack of sumberdya human factor in this regardabout jobs and tax collection object retribution on the field, so that the required data in the targetsetting is not available, it is due to the lack of a dedicated budget to pay the counterparty tocollect data in the field, and 3) lack of infrastructure, this factor with regard to data collectionfacilities required so that taxpayers are less than optimal data collection acquisition.